Tahlîlu Taghyîri Ma’nâ Kalimâti al-‘Arabiyyati Ilâ al-Indunîsiyyati fî Kitâbi Arkhabîla li al-Kalimâti al-Musta’ârati al-Arabiyyati al-Indunîsiyyati - Fitri, Safira; Suparmanto, Suparmanto; Warseto, Andri (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Purpose-This research discusses about the change in the meaning of Arabic in Indonesian in Arabic-Indonesian absorption word book Arkhabil. The purpose of this research to know the changes the meaning of Arabic in Indonesian in Arabic-Indonesian absorption word book Arkhabil, the change factors and their forms. Design/Methodology/Approach-This research is a library research and this research is a qualitative research. The analytical method used is the theory of Milles and Huberman. Findings-The results of this researc indicate that in the arkhabil Arabic-Indonesian absorption word book, 83 (eightty three) Arabic vocabulary in Indonesian were found, namely those underwent changes. From 83 (eightty three) vocabulary words, the meaning changes were classified based on the theory, including 37 (thirty seven) vocabulary change in meaning widening, 29 (twenty nine) vocabulary change in meaning narrowed, and 17 (seventeen) vocabulary change in meaning totally. Reseach Limitatio/ Implication-The limitation of the problem in this study focuses on changes in the meaning of Arabic words in Indonesian which are found in Arkhabil's book, Arabic-Indonesian absorption words